Math, asked by crazy234519, 10 months ago

plz help urgent!!! plzzzzz​

Attachments:

Answers

Answered by Bhavya2706
1

Answer:

16 × 2^n+1 - 4 × 2^n

= __________________

16 × 2^n+2 - 2 × 2^n+2

2^4 × 2^n+1 - 2^2 × 2^n

= ____________________

2^4 × 2^n+2 - 2 × 2^n+2

2^(4+n+1) - 2^(2+n)

= _________________

2^(4+n+2) - 2^(1+n+2)

2^(n+5) - 2^(2+n)

= ______________

2^(n+6) - 2^(n+3)

n + 5 - n - 2

= __________

n + 6 - n - 3

5 - 2

= ____

6 - 3

3

= __

3

= 1

Hope my Answer Is Correct

Similar questions